Aberrant functional connectivity and the intrinsic activity of primary visual network and their relationship with adolescent atypical depression symptoms - Li, Yaoyao; Liu, Xiaoyan; Liu, Hanying; Tang, Bing; Xie, Jize; Ma, Chunhe; Yu, Yingyi; Wu, Sha; Li, Yi (Frontiers in Psychiatry, 2025)
BackgroundThe pathophysiological mechanisms of adolescent atypical depression (A-D) remain unclear. This study used resting-state functional magnetic resonance imaging (rs-fMRI) and independent component analysis (ICA) to compare functional network connectivity (FNC) and intrinsic brain activity between healthy control, A-D, and non-atypical depression (N-AD) adolescents.MethodsFifteen healthy control (HC), 17 A-D, and 18 N-AD adolescents underwent rs-fMRI. Clinical symptoms were assessed using the 30-item Inventory of Depressive Symptomatology (IDS-30R). ICA was employed to analyze internetwork FNC and fractional amplitude of low-frequency fluctuations (fALFF).ResultsThe A-D group exhibited decreased connectivity between the primary visual (IC4) and visuospatial (IC10) networks but increased connectivity between IC4 and the sensorimotor network (IC11), and between the ventral and dorsal default mode networks (IC8 and IC17, respectively). Higher fALFF values were found in the right fusiform face area and left superior occipital gyrus of the A-D group than the N-AD group. Increased appetite correlated positively with IC4–IC10 connectivity (r = 0.573, p = 0.016), and interpersonal rejection sensitivity was correlated with fALFF in the right fusiform area (r = 0.625, p = 0.007).ConclusionAberrant functional connectivity of the visual network and altered activity in visual-processing regions are associated with specific A-D symptoms, providing new insights into its neurophysiology.